Evaluación del nivel de excelencia de los procesos claves en la empresa KEYTEL S.A. - De La Rosa Mora, Kathya Jacqueline (2023)
In this work a descriptive, field and documentary research was presented, in which analytical, synthetic, inductive and deductive tools were used in order to perform an internal analysis, through interviews and a survey to the company's workers and an external analysis through a PESTEL analysis, in which it was evidenced that the company's current performance does not guarantee the efficiency and quality of the services provided, mainly due to the lack of a plan. On the other hand, it is expected that the automotive sector will continue to grow, thanks to the policies being implemented in the country. A process management model was established, with strategic planning, purchasing management, sales management and support processes being key to the company's operations. When applying the integral indicator of the level of excellence of the company's key processes, it was found that the purchasing and sales management processes were deficient. Therefore, through a root-cause analysis, the failures in this process were determined. Solutions were proposed for an improvement plan, which was defined by means of the 5w+2H tool, showing as the high benefit and low cost option an investment of $4,006 for the execution of the solutions.